Longitudinal Assessment of Neurocognitive Outcomes in Survivors of Childhood Acute Lymphoblastic Leukemia Treated on a Contemporary Chemotherapy Protocol - Lisa M. Jacola; Kevin R. Krull; Ching‐Hon Pui; Deqing Pei; Cheng Cheng; Wilburn E. Reddick; Heather M. Conklin (2016)
Purpose Survivors of childhood acute lymphoblastic leukemia (ALL) treated with CNS-directed chemotherapy are at risk for neurocognitive deficits. Prospective longitudinal studies are needed to clarify the neurodevelopmental trajectory in this vulnerable population. Methods Patients enrolled in the St. Jude Total Therapy Study XV, which omitted prophylactic cranial radiation therapy in all patients, completed comprehensive neuropsychological assessments at induction (n = 142), end of maintenance (n = 243), and 2 years after completion of therapy (n = 211). We report on longitudinal change in neurocognitive function and predictors of neurocognitive outcomes 2 years after completing therapy. Results Neurocognitive function was largely age appropriate 2 years after completing therapy; however, the overall group demonstrated significant attention deficits and a significantly greater frequency of learning problems as compared with national normative data (all P ≤ .005). Higher-intensity CNS-directed chemotherapy conferred elevated risk for difficulties in attention, processing speed, and academics (all P ≤ .01). The rate and direction of change in performance and caregiver-reported attention difficulties differed significantly by age at diagnosis and sex. End-of-therapy attention problems predicted lower academic scores 2 years later, with small to moderate effect sizes (│r│= 0.17 to 0.25, all P ≤ .05). Conclusion Two years after chemotherapy-only treatment, neurocognitive function is largely age appropriate. Nonetheless, survivors remain at elevated risk for attention problems that impact real-world functioning. Attention problems at the end of therapy predicted decreased academics 2 years later, suggesting an amplified functional impact of discrete neurocognitive difficulties. Age at diagnosis and patient sex may alter neurocognitive development in survivors of childhood ALL treated with chemotherapy-only protocols.